Political Loyalty and Welfare Distribution under Crony Capitalism in Nigeria: An Empirical Political Economy Analysis - Gbolahan Solomon Osho; Onochie Jude Dieli (ASHA Publishing, 2026)
Political loyalty remains a defining feature of many developing political systems where access to economic opportunities is closely linked to relationships with governing elites. In Nigeria, the interaction between political networks and economic outcomes reflects a broader structure often described as crony capitalism, in which informal connections shape the allocation of state resources. This study examines how political loyalty influences welfare outcomes in Nigeria’s political ecosystem by focusing on access to government contracts, public-sector appointments, and related economic advantages. Using a panel dataset constructed from public records and governance indicators, the study employs econometric analysis to evaluate the relationship between political connections and measurable welfare outcomes. The findings reveal a strong, statistically significant association between political loyalty and improved economic welfare, suggesting that individuals and firms embedded in elite networks are more likely to benefit from state-mediated opportunities. At the same time, the results indicate that such patterns may contribute to unequal access to economic resources and weaken institutional accountability. By providing empirical evidence on the welfare implications of political loyalty, the study advances the literature on patronage politics and political economy in emerging democracies. The findings also highlight the importance of institutional reforms to promote transparency, strengthen governance structures, and ensure that economic opportunities are allocated through fair and competitive processes rather than through informal networks of political allegiance.